Strategi Kepemimpinan Instruksional Dalam Meningkatkan Profesionalisme Guru: Tinjauan Sistematik - Irvan Fauzi; Mu’alimin Mu’alimin; Mulyono Mulyono (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The instructional leadership of school principals is a strategic factor in improving the quality of education, particularly in shaping teacher performance and professionalism. In the context of modern educational challenges, school principals do not only act as administrative managers but also as educational leaders capable of guiding, mentoring, and developing teachers' capacities. This study aims to identify the influence of instructional leadership on teachers' performance and professionalism, as well as to uncover the dominant leadership strategies used in schools. The research questions addressed are: (1) How does instructional leadership influence teacher performance and professionalism? and (2) What are the dominant instructional leadership strategies in improving education quality? The study method uses a systematic literature review (SLR) approach by searching articles through Google Scholar and Publish or Perish (PoP) using the keyword ‘guided inquiry search.’ Out of a total of 50 articles, five main articles were analysed in depth. The findings indicate that instructional leadership significantly influences teachers' work motivation, self-efficacy, and professional development. The most dominant strategies include academic supervision, strengthening the school's vision, and fostering a collaborative work environment. This study underscores the urgency of strengthening the instructional role of school principals and recommends further studies based on meta-analysis and a cross-national contextual approach.